2021
DOI: 10.3390/microorganisms9102095
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Sac Microbiome in Infectious Conjunctivitis

Abstract: Acute bacterial conjunctival infections are common, and this study identified the conjunctival bacterial community in infectious conjunctivitis cases seen at the outpatient clinic of Khanh Hoa General Hospital in Nha Trang, Vietnam from October 2016 through December 2017. Conjunctival swabs were collected and tested using conventional culture, PCR, and 16S ribosomal RNA sequencing. The study included 47 randomly selected patients. More than 98% of all DNA reads represented five bacterial phyla. Three of these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, the bovine ocular microbial community is a potential new target for manipulation, due to diseases such as IBK ( Brown et al, 1998 ), which is a significant health issue affecting the beef cattle industry. Human studies suggest that the ocular surface microbiota is associated with ocular health ( Matysiak et al, 2021 ; Mohamed et al, 2021 ), and that a healthy ocular microbiota may provide resistance against colonization from infectious agents ( Teweldemedhin et al, 2017 ; Chiang and Chern, 2022 ). While the association of the ocular microbiota with IBK is yet to be determined, a recent study revealed a relative greater abundance of Moraxella spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bovine ocular microbial community is a potential new target for manipulation, due to diseases such as IBK ( Brown et al, 1998 ), which is a significant health issue affecting the beef cattle industry. Human studies suggest that the ocular surface microbiota is associated with ocular health ( Matysiak et al, 2021 ; Mohamed et al, 2021 ), and that a healthy ocular microbiota may provide resistance against colonization from infectious agents ( Teweldemedhin et al, 2017 ; Chiang and Chern, 2022 ). While the association of the ocular microbiota with IBK is yet to be determined, a recent study revealed a relative greater abundance of Moraxella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies suggest that the ocular surface microbiota is associated with ocular health (80,81), and that a healthy ocular microbiota may provide resistance against colonization from infectious agents (82,83). While the association of the ocular microbiota with IBK is yet to be determined, a recent study revealed a relative greater abundance of Moraxella spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bovine ocular microbial community is a potential new target for manipulation, due to diseases such as IBK (79), which is a significant health issue affecting the beef cattle industry. Human studies suggest that the ocular surface microbiota is associated with ocular health (80, 81), and that a healthy ocular microbiota may provide resistance against colonization from infectious agents (82, 83). While the association of the ocular microbiota with IBK is yet to be determined, a recent study revealed a relative greater abundance of Moraxella spp.…”
Section: Discussionmentioning
confidence: 99%